Assessment of nutritional value and quantitative analysis of bioactive phytochemicals through targeted LC‐MS/MS method in selected scented and pigmented rice varietals. Issue 6 (29th May 2020) - Choudhury, Paramita; Dutta, Krishna N.; Singh, Akanksha; Malakar, Dipankar; Pillai, Manoj; Talukdar, Narayan C.; Samanta, Suman Kumar; Devi, Rajlakshmi
Abstract : Abstract: Scented (joha) and black rice indigenous to northeast region (NER) of India are the two among 40, 000 varieties of species Oryza sativa, prevalent for its great aroma, medicinal property, and/or equally noteworthy taste. Biochemical and target‐based liquid chromatography mass spectrometry (LCMS) analysis was performed to identify and quantify the different phytonutrients from the selected rice grains of those two varieties. Biochemical assay revealed that the selected black rice (Chakhao Amubi) contains ∼1.8‐fold higher amount of total phenolic and ∼2.3‐fold higher amount of total flavonoid than the scented rice grain (Kon joha). The total starch content was significantly lower in scented rice in comparison to black rice grain. The health beneficial ratio of ω‐6/ω‐3 essential unsaturated fatty acid is notably better in scented rice grain than black rice grain. The targeted LC‐MS/MS analysis confirms the presence of oryzanol and ferulic acid in both the samples. The presence of 4‐hydroxy benzoic acid, apigenin, tricin, avenasterol, coumarin, coumaric acid, phenyl alanine, caffeic acid, and α‐tocophenol were confirmed in the scented rice, whereas the black rice confirms the presence of protocatechuic acid and dehydroxy myricetin. Further the quantitative analysis showed that the lipids lysophosphatidylinositol (LPI) 16:0, lysophosphatidyl ethanolamine (LPE) 14:0, lysophosphatidyl choline (LPC) 18:2, LPE 18:2, phosphatidyl etanolamine (PE), along with oryzanol, hydroxy docosanoic acid are at least threefold higher in scented rice varietal; whereas, in Chakhao Amubi, the content of petunidin galactoside, LMMPE18:2, PC14:0 are higher than the scented rice grain. In conclusion, different phytonutrients including phenol, polyphenol, and flavonoid have been identified as bioactive phytochemicals in selected rice varietals. Practical Application: This work will provide the information about the nutritional benefit of studied rice varietals. The used targeted LC‐MS/MS analysis will provide the one‐step information about the bioactive phytochemicals. Overall, this study will help to commercialize those varieties with proper scientific evidences.